Scale-invariant alternatives to general relativity: III. The inflation-dark energy connection - Casas, Santiago; Pauly, Martin (Physical review, 2019)
We discuss the cosmological phenomenology of biscalar-tensor models displaying a maximally symmetric Einstein-frame kinetic sector and constructed on the basis of scale symmetry and volume-preserving diffeomorphisms. These theories contain a single dimensionful parameter Λ0—associated with the invariance under the aforementioned restricted coordinate transformations—and a massless dilaton field. At large field values these scenarios lead to inflation with no generation of isocurvature perturbations. The corresponding predictions depend only on two dimensionless parameters, which characterize the curvature of the field manifold and the leading-order behavior of the inflationary potential. For Λ0=0 the scale symmetry is unbroken and the dilaton admits only derivative couplings to matter, evading all fifth-force constraints. For Λ0≠0 the field acquires a runaway potential that can support a dark-energy-dominated era at late times. We confront a minimalistic realization of this appealing framework with observations using a Markov chain Monte Carlo approach, with likelihoods from present baryon acoustic oscillation, type Ia supernova, and cosmic microwave background data. A Bayesian model comparison indicates a preference for the considered model over ΛCDM, under certain assumptions for the priors. The impact of possible consistency relations among the early and late Universe dynamics that can appear within this setting is discussed with the use of correlation matrices. The results indicate that a precise determination of the inflationary observables and the dark energy equation of state could significantly constrain the model parameters.